Development of models and improvement of methods for formalization of design problems and automating technical and operational works of railway stations - Mailybayev, Yersaiyn; Muratbekova, Gulzhan; Altayeva, Zhanar; Zhatkanbayev, Orazbay (Eastern-European Journal of Enterprise Technologies, 2022)
The object of research is the processes of automation of the technical and operational assessment of railway stations (RWS). Research solves the problem of developing models, methods and information technologies to automate the process of technical and operational assessment of the work of RWS. As a result of the study, the following results were obtained: Analysis of scientific papers on the problem of automating the work of RWS. Development of new method and mathematical models to automate the task. Development of new descriptions for the technological processes (TechP) of the RWS based on visual programming methods. Development of simulation models for the automation of railway infrastructure management task. The UML diagrams of state and activity have been adapted in order to represent the RWS operation technology. When formalizing the description of the RWS, the state diagrams are submitted taking into account the specifics of the description of the change in the phases of servicing objects in the process of TechP of individual objects maintenance. It is shown that the state diagram for the RWS is a state machine (SM) that models the sequence of changing the states of an object. The detalization of the behavior of objects serviced at the RWS has been completed. Detalization is performed using diagrams of activity. The diagrams of activity are used to formally describe the technical support with objects and executors of work on the railway. The scientific results obtained in the article, as well as new and improved models and methods, can be used in the development, improvement and formalization of the TechP of the RWS, research methods for informatization and automation objects on the railways of the Republic of Kazakhstan.